Changes in smoking and alcohol consumption during COVID-19-related lockdown: a cross-sectional study in France. (7th April 2021) - Guignard, Romain; Andler, Raphaël; Quatremère, Guillemette; Pasquereau, Anne; du Roscoät, Enguerrand; Arwidson, Pierre; Berlin, Ivan; Nguyen-Thanh, Viêt
Abstract: Background: In many countries, lockdown measures were implemented to curb the COVID-19 pandemic. This situation may have an impact on mental health, tobacco smoking and alcohol consumption. The aim of this research report is therefore to describe changes in tobacco and alcohol consumption in the general French population during the first 2 weeks of lockdown and identify any associated factors. Methods: Self-reported changes in smoking and alcohol consumption following the lockdown implemented in France on 17 March 2020 were collected from 2003 respondents aged 18 years and older in an online cross-sectional survey carried out from 30 March to 1 April 2020. Anxiety and depression levels were assessed using the Hospital Anxiety and Depression Scale. Results: Among current smokers, 26.7% reported an increase in their tobacco consumption since lockdown and 18.6% reported a decrease, while it remained stable for 54.7%. The increase in tobacco consumption was associated with an age of 18–34 years, a high level of education, and anxiety. Among alcohol drinkers, 10.7% reported an increase in their alcohol consumption since lockdown and 24.4% reported a decrease, while it remained stable for 64.8%. The increase in alcohol consumption was associated with an age of 18–49 years, living in cities of more than 100 000 inhabitants, a high socio-professional category, and a depressive mood. Conclusions: The national lockdown implemented in France during the COVID-19 pandemic influenced tobacco and alcohol consumption in different ways according to sociodemographic group and mental health.